Lipid metabolism disorder in diabetic kidney disease - Han, Yi-Zhen; Du, Bo-Xuan; Zhu, Xing-Yu; Wang, Yang-Zhi-Yuan; Zheng, Hui-Juan; Liu, Wei-Jing (Frontiers in Endocrinology, 2024)
Diabetic kidney disease (DKD), a significant complication associated with diabetes mellitus, presents limited treatment options. The progression of DKD is marked by substantial lipid disturbances, including alterations in triglycerides, cholesterol, sphingolipids, phospholipids, lipid droplets, and bile acids (BAs). Altered lipid metabolism serves as a crucial pathogenic mechanism in DKD, potentially intertwined with cellular ferroptosis, lipophagy, lipid metabolism reprogramming, and immune modulation of gut microbiota (thus impacting the liver-kidney axis). The elucidation of these mechanisms opens new potential therapeutic pathways for DKD management. This research explores the link between lipid metabolism disruptions and DKD onset.